Corneoscleral transplantation for end stage corneal disease. Issue 11 (1st November 1998) - Hirst, Lawrence W; Lee, Graham A
Abstract : AIM: To describe the prognosis and complications of corneoscleral transplantation in the management of end stage eye disease. METHODS: A case series is presented of 23 patients who have undergone corneoscleral transplantation (⩾11 mm). Patients were examined for visual acuity, intraocular pressure, recurrence of disease process, epithelialisation of the graft, signs of rejection, and other potential complications. RESULTS: 14 patients retained their eye, with six maintaining a clear graft. Vision ranged from 6/30 to no perception of light. 13 patients developed glaucoma (range 25–69 mm Hg), with six patients requiring surgical intervention. 12 patients required tarsorrhaphy to promote epithelialisation. Only two grafts resulted in typical rejection. CONCLUSIONS: The technique of corneoscleral transplantation can salvage otherwise end stage eye disease, but the results are poor with respect to maintenance of vision. These patients need careful follow up because of potential complications of glaucoma, epithelial defects, rejection, and recurrence of disease.